Challenging the relationship of grip strength with cognitive status in older adults. (24th October 2020) - Hooyman, Andrew; Malek‐Ahmadi, Michael; Fauth, Elizabeth B.; Schaefer, Sydney Y.
Abstract: Objective: Grip strength is a widely used motor assessment in ageing research and has repeatedly been shown to be associated with cognition. It has been proposed that grip strength could enhance cognitive screening in experimental or clinical research, but this study uses multiple data‐driven approaches to caution against this interpretation. Furthermore, we introduce an alternative motor assessment, comparable to grip dynamometry, but has a more robust relationship with cognition among older adults. Design: Associations between grip strength and cognition (measured with the Montreal Cognitive Assessment) were analysed cross sectionally using multivariate regression in two datasets: (1) The Irish LongituDinal Study on Ageing (TILDA; N = 5, 980, community‐dwelling adults ages 49–80) and (2) an experimental dataset ( N = 250, community‐dwelling adults aged 39–98). Additional statistical simulations on TILDA tested how ceiling effects or skewness in these variables influenced these associations for quality control. Results: Grip strength was significantly but weakly associated with cognition, consistent with previous studies. Simulations revealed this was not due to skewness/ceiling effects. Conversely, a new alternative motor assessment (functional reaching [FR]) had a stronger, more robust and more sensitive relationship with cognition compared to grip strength. Conclusions: Grip strength should be cautiously interpreted as being associated with cognition. However, FR may have a stronger and clinically useful relationship with cognition.